Multiplicative Integral Measure of Evaluating the Energy Security Situation - Fedorchenko S.; Fedorchenko G. (Problems of the Regional Energetics)
The approach to the evaluation of the integral measure estimation of energy safety with using a generalized utility Harrington-Menchers’s function is considered in this paper. The algorithm of formation of the integral index includes the use of both additive and multiplicative measures. To test data on the energy security were used referred to Transnistria. It is presented an example of the construction of such a measure. During carrying out of this work the analysis of the indicators recommended in the open literature as components of energy safety is made. It is shown that a significant part of these indicators is closely linked with others.